The impact of psychological pressure and psychological traits on performance - An experimental evidence of penalties in handball - Buehren, C.; Traege, L. (MAGKS Papers on Economics, 2020)
Our handball penalty field experiment analyses the influence of psychological traits and pressure on individual performance in sequential tournaments. We use a short ABBA-sequence with four throws for each subject and observe an average score rate of 60% in our sample of amateur league players. On game level, we find a weak and insignificant first-mover advantage that becomes stronger and significant if we control for psychological traits and pressure. On shot level, we also find no significant first-mover advantage on average. However, confident individuals have a higher scoring rate in the role of player A and less confident individuals in the role of player B. Moreover, ceteris paribus, player A scores more goals than player B under tournament incentives. Whereas self-esteem increases the probability to throw a goal in our experiment, risk-taking reduces it.